Postmodern psychology of personality - Garifullin, Ramil R. (Opción, 2019)
This article provides an analysis of the postmodern psychology of personality and outlines its main contours formed by means of textual, nomadological, schizoanalytical, narratologic, simulative and synergistic approaches. On the basis of the analysis of a great number of works, we show that the majority of the studied psychological mechanisms are secondary reconstructions induced by the main vector of psychical dynamics, which has barely been studied in psychology. As we show, to achieve a more effective psycho-correction of an addicted person, it is necessary to take into account the fundamental unpredictability and paradoxical character of this person’s future semantic processes.